A method for preparing a low-resistance flexible graphite plate-attached flow channel for a liquid flow battery
By using low-resistance conductive silver glue and carbon black conductive glue in the flow battery, the problems of high contact resistance between the flexible graphite plate and the runner plate and electrolyte contamination are solved, and more efficient electron transmission and longer service life are achieved.
Patent Information
- Application Number
- CN202510026469.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-08
AI Technical Summary
The contact resistance between the flexible graphite plate and the runner plate in existing flow batteries is high, which affects electron transmission, and the use of conductive adhesives may lead to electrolyte contamination.
Low resistance conductive silver glue is used to combine with carbon black conductive glue, which is used to adhere to the flexible graphite plate and the runner plate, reduce contact resistance, and prevent electrolyte contamination by heating and curing.
It effectively reduces the contact resistance between the flexible graphite plate and the runner plate, improves the operating efficiency and reliability of the battery stack, extends the service life, and avoids electrolyte contamination.
Smart Images

Figure CN119447348B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of energy storage, and in particular to a method for preparing a low-resistance flexible graphite plate-attached flow channel for a liquid flow battery. Background Art
[0002] Renewable energy sources such as solar energy and wind energy have intermittent and unstable power generation problems and cannot be directly connected to the power grid. According to the basic situation of renewable energy generation and output, there is a demand for practical balanced power generation. To achieve this demand, appropriate electrochemical energy storage equipment must be invested in the power grid.
[0003] Electrochemical energy storage has the characteristics of pollution-free operation, high efficiency, flexible power and energy characteristics that can meet the functions of different power grids, long cycle life, low maintenance cost, and is not restricted by terrain and environment. It can directly store and release electrical energy, making it an ideal energy storage technology. Liquid flow batteries have the characteristics of low cost, long life, and high energy efficiency, and are considered to be the development direction of large-scale electrochemical energy storage. In the past 40 years of research and development, iron-chromium system liquid flow batteries have been close to full commercialization and have been widely used in emergency continuous power supply facilities, industrial batteries, electric traction, independent applications, and electric load balancing.
[0004] The bipolar plates in flow batteries provide electrolyte flow channels and establish current paths between the positive and negative electrodes. They are generally divided into flexible graphite plates and hard graphite plates. Flexible graphite plates have the advantages of low cost and easy processing, but their thickness is small and it is difficult to etch electrolyte flow channels on their surfaces. Therefore, a flexible graphite plate is first stamped and die-cut into a flow channel plate, and then combined with another flexible graphite plate to form a bipolar plate. However, the high contact resistance between the two plates is not conducive to electron transmission. If conductive glue is used for bonding, the electrolyte may be contaminated by metal ions in the glue. Therefore, how to reduce its contact resistance is an urgent problem to be solved. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a method for preparing a low-resistance flexible graphite plate attached to a flow channel for a liquid flow battery, and prepares a low-resistance conductive silver paste, which is compounded with a carbon black conductive paste and used for bonding the flexible graphite plate to the flow channel plate, thereby reducing the contact resistance between the flexible graphite plate and the flow channel plate; at the same time, the conductive silver paste is effectively prevented from contacting the electrolyte, thereby preventing the electrolyte from being contaminated by metal ions in the conductive silver paste, thereby solving the problems mentioned in the above background technology.
[0006] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a method for preparing a low-resistance flexible graphite plate with a flow channel for a liquid flow battery, comprising the following steps: performing surface pretreatment on the flexible graphite plate and the flow channel plate, then using a dispensing device to evenly apply a 0.1-0.3 mm thick conductive silver glue on the flexible graphite plate according to the contour of the flow channel plate, and pressing the flow channel plate onto the flexible graphite plate; then using a dispensing device to adhere carbon black conductive glue around the contact surface between the flexible graphite plate and the flow channel plate, with a thickness of 0.4-0.7 mm, and finally heating to 80-120°C on a heating table, and maintaining hot pressing for 1-2 hours to make them bonded, and after heating is completed, standing for 1 hour before rinsing and drying.
[0007] Preferably, the flexible graphite plate has a thickness of 0.8±0.04 mm, a resistivity of ≤3.3 mΩ·cm, and is die-cut into a rounded rectangle of 1 m×0.55 m; the surface pretreatment is grinding and polishing the surface of the flexible graphite plate using an abrasive and a polishing wheel.
[0008] Preferably, the flow channel plate is formed by one-time stamping and die-cutting of a flexible graphite plate, the flow channel width is 1.5 cm, the length is 55 cm, and the flow channel wall thickness is 1.5 cm; the surface pretreatment is to grind and polish the surface of the flow channel plate using an abrasive and a polishing wheel.
[0009] Preferably, the conductive silver paste is composed of the following components in parts by weight: 20 parts of resin, 65 parts of silver powder, 10 parts of solvent, 3 parts of curing agent, 1 part of dispersant, and 1 part of filler.
[0010] Preferably, the resin is epoxy resin, the solvent is ethanol, the curing agent is diethylenetriamine, and the filler is silicon dioxide.
[0011] Preferably, the preparation of the conductive silver paste includes the following steps:
[0012] Step S1, mixing silver powder and dispersant evenly to ensure that silver particles are fully dispersed to obtain a mixture A;
[0013] Step S2, dissolving the resin in a solvent and stirring evenly to obtain a resin solution;
[0014] Step S3, adding mixture A to the resin solution and stirring thoroughly to obtain mixture B;
[0015] Step S4, adding a curing agent to the mixture B, continuing to stir until uniform, filtering the mixture to remove undispersed particles and other impurities, and obtaining a mixture C, i.e., conductive silver paste.
[0016] Preferably, the carbon black conductive adhesive is composed of the following components in parts by weight: 30-50 parts of resin, 10-30 parts of conductive carbon black, 10-20 parts of solvent, 5-10 parts of curing agent, 1-5 parts of dispersant, 5-15 parts of filler, and 1-5 parts of antioxidant.
[0017] Preferably, the resin is epoxy resin, the solvent is acetone, the curing agent is diethylenetriamine, and the filler is silicon dioxide.
[0018] Preferably, the preparation of the carbon black conductive adhesive includes the following steps:
[0019] Step 1, mixing the carbon black conductor and the dispersant evenly to ensure that the carbon black particles are fully dispersed to obtain a mixture 1;
[0020] Step 2, dissolving the resin in a solvent and stirring evenly to obtain a resin solution;
[0021] Step 3, adding mixture 1 to the resin solution and stirring thoroughly to obtain mixture 2;
[0022] Step 4: Add the curing agent, filler and antioxidant to the mixture 2, continue stirring until it is uniform, filter the mixture to remove undispersed particles and other impurities, and obtain the mixture 3, i.e., the carbon black conductive adhesive.
[0023] The beneficial effects of the present invention are as follows: the method of the present invention prepares a low-resistance conductive silver paste, and then compounds it with a carbon black conductive paste, which is used together for bonding a flexible graphite plate to a flow channel plate; the method of the present invention reduces the contact resistance between the flexible graphite plate and the flow channel plate, improves the operating efficiency of the battery stack, saves costs, has a firm structure, and effectively prevents the conductive silver paste from contacting the electrolyte, thereby preventing the electrolyte from being contaminated by metal ions in the conductive silver paste, thereby improving the reliability of the flow battery stack, extending the service life of the flow battery stack, and having excellent application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 An exploded view of a flexible graphite plate attached to a flow channel in an embodiment of the present invention;
[0025] Figure 2 A side view of a flexible graphite plate attached to a flow channel in an embodiment of the present invention;
[0026] In the figure, 1-flexible graphite plate; 2-flow channel plate; 3-carbon black conductive glue; 4-conductive silver glue. DETAILED DESCRIPTION
[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] The present embodiment provides a method for preparing a low-resistance flexible graphite plate-attached flow channel for a liquid flow battery, such as Figure 1 and Figure 2 As shown, the low-resistance flexible graphite plate pasted flow channel includes: a composite glue of conductive silver glue 4 and carbon black conductive glue 3, a flexible graphite plate 1, and a flow channel plate 2.
[0030] The thickness of the flexible graphite sheet is 0.8±0.04 mm, the resistivity is ≤3.3 mΩ·cm, and it is die-cut into a rounded rectangle of 1 m×0.55 m. The surface pretreatment is to grind and polish the surface of the flexible graphite sheet using an abrasive and a polishing wheel.
[0031] The flow channel plate is made of a flexible graphite plate by one-time stamping and die-cutting. The flow channel is 1.5 cm wide, 55 cm long, and 1.5 cm thick. The surface pretreatment is to grind and polish the surface of the flow channel plate using abrasives and polishing wheels.
[0032] The conductive silver paste 4 is composed of the following components in parts by weight: 20 parts of resin, 65 parts of silver powder, 10 parts of solvent, 3 parts of curing agent, 1 part of dispersant, and 1 part of filler.
[0033] Furthermore, the resin is epoxy resin, the solvent is ethanol, the curing agent is diethylenetriamine, and the filler is silicon dioxide.
[0034] The preparation of conductive silver paste includes the following:
[0035] Step S1, mixing silver powder and dispersant evenly to ensure that silver particles are fully dispersed to obtain a mixture A;
[0036] Step S2, dissolving the resin in a solvent and stirring evenly to obtain a resin solution;
[0037] Step S3, adding mixture A to the resin solution and stirring thoroughly to obtain mixture B;
[0038] Step S4, adding a curing agent to the mixture B, continuing to stir until uniform, filtering the mixture to remove undispersed particles and other impurities, and obtaining a mixture C, i.e., conductive silver paste.
[0039] Furthermore, the carbon black conductive adhesive 3 is composed of the following components in parts by weight: 30-50 parts of resin, 10-30 parts of conductive carbon black, 10-20 parts of solvent, 5-10 parts of curing agent, 1-5 parts of dispersant, 5-15 parts of filler, and 1-5 parts of antioxidant.
[0040] The resin is epoxy resin, the solvent is acetone, the curing agent is diethylenetriamine, the dispersant is ammonium polyacrylate, the antioxidant is BHT, and the filler is silicon dioxide.
[0041] Further, the preparation of the carbon black conductive adhesive 3 includes the following steps:
[0042] Step 1, mixing the carbon black conductor and the dispersant evenly to ensure that the carbon black particles are fully dispersed to obtain a mixture 1;
[0043] Step 2, dissolving the resin in a solvent and stirring evenly to obtain a resin solution;
[0044] Step 3, adding mixture 1 to the resin solution and stirring thoroughly to obtain mixture 2;
[0045] Step 4: Add the curing agent, filler and antioxidant to the mixture 2, continue stirring until it is uniform, filter the mixture to remove undispersed particles and other impurities, and obtain the mixture 3, i.e., the carbon black conductive adhesive.
[0046] The preparation of the low-resistance flexible graphite plate attached to the flow channel in the embodiment of the present invention includes: performing surface pretreatment on the flexible graphite plate and the flow channel plate, then using a dispensing device / dispensing machine to evenly apply 0.1-0.3 mm thick conductive silver glue on the flexible graphite plate according to the contour of the flow channel plate, and pressing the flow channel plate onto the flexible graphite plate; then using a dispensing device / dispensing machine to adhere carbon black conductive glue around the contact surface of the flexible graphite plate and the flow channel plate, with a thickness of 0.4-0.7 mm (thicker than the conductive silver glue for sealing), and finally heating to 80-120°C on a heating table (the high temperature causes the resin in the conductive glue to react with the curing agent and solidify, and it will not soften when heated again), and maintaining hot pressing for 1-2 hours to make it bonded, and after heating is completed, let it stand for 1 hour before rinsing and drying.
[0047] Comparative Example 1
[0048] The flexible graphite plate pasted flow channel of this comparative example 1 comprises: a carbon black conductive adhesive, a flexible graphite plate, and a flow channel plate;
[0049] The carbon black conductive adhesive is composed of the following raw materials in parts by mass: 30 parts of resin, 30 parts of conductive carbon black, 20 parts of solvent, 5 parts of curing agent, 5 parts of dispersant, 5 parts of filler, and 5 parts of antioxidant;
[0050] The resin is epoxy resin, the solvent is acetone, the curing agent is diethylenetriamine, the dispersant is ammonium polyacrylate, the antioxidant is BHT, and the filler is silicon dioxide. The carbon black conductive adhesive is prepared as follows:
[0051] 1) Premixing: Mix the carbon black and dispersant evenly to ensure that the carbon black particles are fully dispersed.
[0052] 2) Dissolve the resin: dissolve the resin in the solvent and stir evenly.
[0053] 3) Mixing: Add the pre-mixed carbon black into the resin solution and stir thoroughly.
[0054] 4) Add curing agent: Add curing agent into the mixture and continue stirring until uniform.
[0055] 5) Add fillers and antioxidants: Add fillers and antioxidants to the mixture and stir well.
[0056] 6) Filtration: If necessary, filter the mixture to remove undispersed particles or other impurities.
[0057] 7) Packaging: Put the mixed conductive carbon black glue into a suitable container and seal it for storage.
[0058] The flexible graphite plate (substrate) has a thickness of 0.8±0.04 mm, a resistivity of ≤3.3 mΩ·cm, is die-cut into a rounded rectangle of 1 m×0.55 m, and the surface is ground and polished using an abrasive and a polishing wheel.
[0059] The flow channel plate is formed by one-time stamping and die-cutting of a flexible graphite plate, the flow channel width is 1.5 cm, the length is 55 cm, and the flow channel wall thickness is 1.5 cm; the surface is ground and polished using an abrasive and a polishing wheel.
[0060] Comparative Example 1 The preparation of the flexible graphite plate attached to the flow channel includes: using a dispensing machine to evenly apply a 0.4-0.7mm thick carbon black conductive glue on the substrate according to the contour of the flow channel plate, and then pressing the flow channel plate onto the substrate. After pasting, heat it on a heating table to 80-120°C (high temperature causes the resin in the conductive glue to react with the curing agent to solidify, and it will not soften if heated again), and keep hot pressing for 1-2 hours to make it bonded. After heating, let it stand for 1 hour, rinse it, and dry it for use.
[0061] Comparative Example 2
[0062] The flexible graphite plate pasted flow channel of this comparative example 2 comprises: a conductive silver paste, a flexible graphite plate, and a flow channel plate;
[0063] The conductive silver paste is composed of the following raw materials in parts by mass: 20 parts of resin, 65 parts of silver powder, 10 parts of solvent, 3 parts of curing agent, 1 part of dispersant, and 1 part of filler.
[0064] The resin is epoxy resin, the solvent is ethanol, the curing agent is diethylenetriamine, and the filler is silicon dioxide. The conductive silver glue is prepared as follows:
[0065] 1) Premixing: Mix the silver powder and dispersant evenly to ensure that the silver particles are fully dispersed.
[0066] 2) Dissolve the resin: dissolve the resin in the solvent and stir evenly.
[0067] 3) Mixing: Add the pre-mixed silver powder into the resin solution and stir thoroughly.
[0068] 4) Add curing agent: Add curing agent into the mixture and continue stirring until uniform.
[0069] 5) Filtration: If necessary, filter the mixture to remove undispersed particles or other impurities.
[0070] 6) Packaging: Put the mixed conductive silver glue into a suitable container and seal it for storage.
[0071] The flexible graphite plate (substrate) has a thickness of 0.8±0.04 mm, a resistivity of ≤3.3 mΩ·cm, is die-cut into a rounded rectangle of 1 m×0.55 m, and the surface is ground and polished using an abrasive and a polishing wheel.
[0072] The flow channel plate is formed by one-time stamping and die-cutting of a flexible graphite plate, the flow channel width is 1.5 cm, the length is 55 cm, and the flow channel wall thickness is 1.5 cm; the surface is ground and polished using an abrasive and a polishing wheel.
[0073] Comparative Example 2 The preparation of the flexible graphite plate attached to the flow channel includes: using a dispensing machine to evenly apply 0.1-0.3 mm thick conductive silver glue on the substrate according to the contour of the flow channel plate, and then pressing the flow channel plate onto the substrate. After pasting, heat it on a heating table to 80-120°C (high temperature causes the resin in the conductive glue to react with the curing agent to solidify, and it will not soften if heated again), and keep hot pressing for 1-2 hours to make it bonded. After heating, let it stand for 1 hour, rinse it, and dry it for use.
[0074] Comparative Example 3
[0075] The flexible graphite plate attached to the flow channel of this comparative example 3 includes: a flexible graphite plate and a flow channel plate.
[0076] The flexible graphite sheet (substrate) had a thickness of 0.8 ± 0.04 mm and a resistivity of ≤ 3.3 mΩ·cm. It was die-cut into a rounded rectangle of 1 m × 0.55 m, and the surface was ground and polished using abrasives and a polishing wheel.
[0077] The flow channel plate is made of a flexible graphite plate by one-time stamping and die-cutting. The flow channel is 1.5 cm wide, 55 cm long, and 1.5 cm thick. The surface is ground and polished using abrasives and polishing wheels.
[0078] Comparative Example 3 The preparation of the flexible graphite plate attached to the flow channel includes: using a press machine to directly press the two plates together under a force of 100 N.
[0079] The flexible graphite plate was tested for flow channel resistance by using a 2×4 flexible graphite plate for a reduced test. A contact resistance meter was used to test the contact resistance and battery energy efficiency of the composite use of conductive silver glue and carbon black conductive glue (Example 1), the use of only carbon black conductive glue (Comparative Example 1), the use of only conductive silver glue (Comparative Example 2), and the use of only pressure bonding two plates (Comparative Example 3). The comparison results are shown in Table 1.
[0080] Table 1 Performance comparison results of Example 1 and various comparative examples
[0081]
[0082] As shown in Table 1, the resistance of Example 1 of the present invention is only 3.098 mΩ, and the energy efficiency is 79.4%; Comparative Example 1 only uses carbon black conductive glue, the resistance increases, and the energy efficiency is 66.7% because the battery resistance is too large; Comparative Example 2 only uses conductive silver glue, although the resistance is close to that of Example 1, the metal in the glue contaminates the electrolyte, resulting in a battery energy efficiency of only 49.4%; Comparative Example 3 only uses pressure bonding, the resistance is the largest, and the energy efficiency is only 53.3%. It can be seen that the method of the present invention reduces the contact resistance between the flexible graphite plate and the flow channel plate, improves the operating efficiency of the battery stack, saves costs, has a firm structure, and effectively prevents the contact between the conductive silver glue and the electrolyte, prevents the electrolyte from being contaminated by the metal ions in the conductive silver glue, improves the reliability of the flow battery stack, and extends the service life of the flow battery stack.
[0083] It should be noted that the embodiments and features of the embodiments of the present invention can be combined with each other without conflict. It should be noted that similar reference numerals and letters represent similar items in the following drawings, so once an item is defined in one drawing, it does not need to be further defined and explained in the subsequent drawings.
[0084] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inside", "outside", etc. indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, or the positions or positional relationships in which the product of the invention is usually placed when in use, or the positions or positional relationships commonly understood by those skilled in the art, which are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", etc. are only used to distinguish the description, and cannot be understood as indicating or implying relative importance.
[0085] In the description of the present invention, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0086] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a low-resistance flexible graphite plate-attached flow channel for a liquid flow battery, characterized in that: The method comprises the following steps: pre-treating the surfaces of the flexible graphite plate and the flow channel plate, and then using a dispensing device to evenly apply a 0.1-0.3 mm thick conductive silver glue on the flexible graphite plate according to the contour of the flow channel plate, and pressing the flow channel plate onto the flexible graphite plate; then using a dispensing device to adhere the carbon black conductive glue around the contact surface between the flexible graphite plate and the flow channel plate, with a thickness of 0.4-0.7 mm, and finally heating to 80-120°C on a heating table, and maintaining hot pressing for 1-2 hours to bond them, and after heating is completed, standing for 1 hour before rinsing and drying.
2. The method for preparing a low-resistance flexible graphite plate-attached flow channel for a flow battery according to claim 1, characterized in that: The flexible graphite plate has a thickness of 0.8±0.04 mm, a resistivity of ≤3.3 mΩ·cm, and is die-cut into a rounded rectangle of 1 m×0.55 m; the surface pretreatment is to grind and polish the surface of the flexible graphite plate using an abrasive and a polishing wheel.
3. The method for preparing a low-resistance flexible graphite plate-attached flow channel for a flow battery according to claim 1, characterized in that: The flow channel plate is formed by one-time stamping and die-cutting of a flexible graphite plate, with a flow channel width of 1.5 cm, a length of 55 cm, and a flow channel wall thickness of 1.5 cm; the surface pretreatment is to grind and polish the surface of the flow channel plate using an abrasive and a polishing wheel.
4. The method for preparing a low-resistance flexible graphite plate-attached flow channel for a flow battery according to claim 1, characterized in that: The conductive silver paste is composed of the following components in parts by weight: 20 parts of resin, 65 parts of silver powder, 10 parts of solvent, 3 parts of curing agent, 1 part of dispersant, and 1 part of filler.
5. The method for preparing a low-resistance flexible graphite plate-attached flow channel for a flow battery according to claim 4, characterized in that: The resin is epoxy resin, the solvent is ethanol, the curing agent is diethylenetriamine, and the filler is silicon dioxide.
6. The method for preparing a low-resistance flexible graphite plate-attached flow channel for a flow battery according to claim 1 or 4, characterized in that: The preparation of the conductive silver paste includes the following steps: Step S1, mixing silver powder and dispersant evenly to ensure that silver particles are fully dispersed to obtain a mixture A; Step S2, dissolving the resin in a solvent and stirring evenly to obtain a resin solution; Step S3, adding mixture A to the resin solution and stirring thoroughly to obtain mixture B; Step S4, adding a curing agent to the mixture B, continuing to stir until uniform, filtering the mixture to remove undispersed particles and other impurities, and obtaining a mixture C, i.e., a conductive silver paste.
7. The method for preparing a low-resistance flexible graphite plate-attached flow channel for a flow battery according to claim 1, characterized in that: The carbon black conductive adhesive is composed of the following components in parts by weight: 30-50 parts of resin, 10-30 parts of conductive carbon black, 10-20 parts of solvent, 5-10 parts of curing agent, 1-5 parts of dispersant, 5-15 parts of filler and 1-5 parts of antioxidant.
8. The method for preparing a low-resistance flexible graphite plate-attached flow channel for a flow battery according to claim 7, characterized in that: The resin is epoxy resin, the solvent is acetone, the curing agent is diethylenetriamine, and the filler is silicon dioxide.
9. The method for preparing a low-resistance flexible graphite plate-attached flow channel for a flow battery according to claim 1 or 7, characterized in that: The preparation of the carbon black conductive adhesive includes the following steps: Step 1, mixing the carbon black conductor and the dispersant evenly to ensure that the carbon black particles are fully dispersed to obtain a mixture 1; Step 2, dissolving the resin in a solvent and stirring evenly to obtain a resin solution; Step 3, adding mixture 1 to the resin solution and stirring thoroughly to obtain mixture 2; Step 4: Add the curing agent, filler and antioxidant to the mixture 2, continue stirring until it is uniform, filter the mixture to remove undispersed particles and other impurities, and obtain the mixture 3, i.e., the carbon black conductive adhesive.
Citation Information
Patent Citations
Bipolar plate for a high-temperature fuel cell, and manufacturing method thereof
CN108172859A
PEM electrolytic cell composite pole plate
CN111041510A